Clinical failure of dalbavancin for MRSA bacteremia in patient with severe obesity and history of IVDU. Issue 3 (March 2022) - Ritchie, Hannah; Aggarwal, Abhimanyu; Schimmel, Jennifer; Lorenzo, Michael P.
Abstract: Dalbavancin is a lipoglycopeptide antibiotic used off-label to treat serious gram-positive infections, including infections secondary to methicillin-resistant Staphylococcus aureus (MRSA). Dalbavancin has unique pharmacokinetic parameters and has a role in therapy for treating vulnerable patients, including intravenous drug users, who have challenges complying with typical care plans for serious infections. While there is data indicating successful clinical use of dalbavancin in patients with history of intravenous drug use as well as pharmacokinetic-pharmacodynamic data assessing dalbavancin in obesity, there is a lack of information regarding clinical effects of dalbavancin in patients with extreme obesity, especially in patients with concomitant drug use. This case report describes a 40-year-old morbidly obese female actively using intravenous drugs who developed prolonged MRSA bacteremia without a recognizable focus. Despite partial treatment with dalbavancin, the patient developed osteomyelitis and discitis of the spine with associated epidural phlegmon, likely complications of the MRSA bacteremia.